Gastrointestinal side effects of triple immunosuppressive therapy evaluated by AC biosusceptometry and electrogastrography in rats - Dallagnol, Denize J. R. [UNESP] (2020)
Background: Triple immunosuppressive therapy is associated with several gastrointestinal disorders. The aim of this study was to investigate the effects induced by the triple immunosuppressive therapy on the gastrointestinal tract of rats. Methods: Male Wistar rats were randomly assigned into three experimental groups: Control: filtered water; TAC + MPS + PRED: treated with Tacrolimus plus Mycophenolate Sodium plus Prednisone; and CSA + AZA + PRED: treated with Cyclosporine plus Azathioprine plus Prednisone. The treatment was done for 14 days by gavage. Gastric emptying and contractility were evaluated by the Alternating Current Biosusceptometry (ACB) and Electrogastrography (EGG). Histological, biochemical and he-matological analyses were also performed. Results: Gastric emptying time was slower in the CSA + AZA + PRED group in comparison with control (p<0.01) and TAC + MPS + PRED groups (p<0.001). Animals treated with TAC + MPS + PRED showed accelerated gastric emptying (p<0.05) compared to control. The amplitude of gastric contractions in both immunosuppressed groups was higher than observed in the control. The frequency of gastric contractions for the CSA + AZA + PRED group was also increased (p<0.01). Results ob-tained by EGG were similar to those recorded with the ACB. The thickness of the circular layer from stomach muscle decreased in both immunosuppressed groups, while the longitudinal layer was reduced only in the CSA + AZA + PRED group. Conclusion: Triple immunosuppressive therapy alters gastric motility, compromises the muscular layers and the association between CSA, AZA, and PRED provokes the major alterations in the structure and gastric function. Specific gastrointestinal side effects resulting from different immunosuppres-sive therapies still need to be elucidated in order to provide more effective and personalized therapy for patients.